2020
DOI: 10.3389/fpsyg.2020.00894
|View full text |Cite
|
Sign up to set email alerts
|

Job Crafting and Performance in Firefighters: The Role of Work Meaning and Work Engagement

Abstract: The Job Demands-Resources (JD-R) model was often utilized as an explanatory framework when investigating the strain process among first responders in general and firefighters in particular. Yet, little is known about the motivational processes whithin firefighters. The aim of this study is to expand the knowledge regarding the motivational process of firefighters by investigating job crafting and introducing work meaning within the motivational framework of the JD-R model, in relation to job performance. A cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 63 publications
2
18
0
3
Order By: Relevance
“…It is worth noting that in our sample, the moderating effect was stronger in relation to hindering job demands, such as administrative hassles and conflicting expectations in the workplace. It is possible that a strong sense of meaning enables individuals to be more engaged [ 37 , 43 , 67 , 68 ] and maintain their focus on the positive and significant aspects of their activity rather than getting stuck on various bureaucratical or procedural inconsistencies and contradictory demands. Nevertheless, our data suggest that even in the case of a military structure, which entails rigid rules, regulations, and orders, administrative hassles and conflicting expectations present significant threats to personnel performance and well-being.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that in our sample, the moderating effect was stronger in relation to hindering job demands, such as administrative hassles and conflicting expectations in the workplace. It is possible that a strong sense of meaning enables individuals to be more engaged [ 37 , 43 , 67 , 68 ] and maintain their focus on the positive and significant aspects of their activity rather than getting stuck on various bureaucratical or procedural inconsistencies and contradictory demands. Nevertheless, our data suggest that even in the case of a military structure, which entails rigid rules, regulations, and orders, administrative hassles and conflicting expectations present significant threats to personnel performance and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled group sessions could be favorable contexts for creating meaning through the flow of ideas and experiences related to various aspects of firefighters’ work and work-related experiences. For instance, our previous research [ 37 ] found that firefighters actively engage in job crafting and consequently shape the meaning that work has in their lives. In conclusion, either through organizational or psychological means, actions taken toward deriving personal significance from work and a broader sense of meaning should be addressed synergistically to aim to prevent burnout symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings can be contrasted with those of other studies, although to date not many have addressed this question. Dan et al [ 11 ], with a sample of 1151 firefighters, found that job crafting could influence engagement levels through the meaning attributed to the job. Furthermore, Vermooten et al [ 29 ] conducted a study with 391 participants and confirmed a model in which a proactive personality influences employees’ job crafting levels.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of continuing research on how the meaning of work can contribute to more engaged employees and how organizations can foster meaning at work through employee characteristics [ 11 ], the main objective of this study is to increase knowledge of the relationship between job crafting and engagement, in order to test the possible effect of the meaning that people give their job and work role on this relationship.…”
Section: Introductionmentioning
confidence: 99%